ICU environmental surfaces are a reservoir of fungi: species distribution in northern Italy. (May 2022) - Prigitano, A.; Perrone, P.M.; Esposto, M.C.; Carnevali, D.; De Nard, F.; Grimoldi, L.; Principi, N.; Cogliati, M.; Castaldi, S.; Romanò, L.
Summary: Background : Preventing and reducing nosocomial infections is a public health goal. Concern about healthcare-associated fungal infections has increased in recent years due to the emergence and spread of new pathogens, increasing antifungal resistance and outbreaks in hospital settings. Aim : To investigate the presence of medically relevant fungal species on environmental surfaces in 12 intensive care units of eight hospitals in Milan, Italy. Methods : Environmental samplings, using contact plates on surfaces near bed stations and medical workstations, were conducted between November 2019 and January 2020. Fungi isolated were identified, and some were tested in vitro for antifungal susceptibility. Findings : In total, 401 environmental samples were collected from 61 bed stations and 17 medical workstations. Positive samples were found in all hospitals except one, with positivity rates ranging from 4% to 24.2%. Filamentous fungi were found mainly on infusion pumps (23.2%) and patient tables (21.2%), whereas yeasts were found mainly on computers (25%) and floors (10.9%). Fungi were isolated from 12% of total samples. Filamentous fungi, mainly Aspergillus fumigatus, grew in 70.8% of positive samples, and yeasts grew in 27.1%, mainly Candida parapsilosis (42.8%) and Candida glabrata (28.6%). Fungi were detected near patients' beds and on surfaces at workstations, indicating potential for environment-to-patient, patient-to-patient and healthcare worker-to-patient transmission. Conclusions : Surveillance in hospital settings through environmental sampling may be an important component of fungal infection prevention.